The Influence of Peer Support and Supervisor Support on Employee Performance Through Teamwork Cohesiveness as a Mediating Variable - Jihan Nur Azizah; Fauji Sanusi; Roni Kambara (Jurnal Bisnis dan Manajemen, 2026)
Employee performance is an important factor in determining the success of organizational operations, particularly in the catering industry. High operational demands and dynamic work conditions may influence employees’ ability to perform their tasks effectively. Therefore, understanding the factors that influence employee performance is important for organizations. This study aims to analyze the influence of peer support and supervisor support on employee performance, with teamwork cohesiveness acting as a mediating variable at Catering Citra Purnama. This study uses a quantitative approach with an explanatory research design. The population consisted of 90 employees of Catering Citra Purnama, with 84 operational employees selected as the research sample using a saturated sampling technique. Data were collected through questionnaires using a 1–10 measurement scale. The data were analyzed using the Partial Least Squares–Structural Equation Modeling method with SmartPLS 3.0 software to examine the relationships between variables and the mediating role of teamwork cohesiveness. The results indicate that peer support has a positive and significant effect on employee performance, whereas supervisor support has a positive but insignificant effect on employee performance. Teamwork cohesiveness has a positive and significant effect on employee performance. Furthermore, both peer support and supervisor support have positive and significant effects on teamwork cohesiveness. Mediation analysis shows that teamwork cohesiveness partially mediates the relationship between peer support and employee performance and fully mediates the relationship between supervisor support and employee performance. These findings highlight the importance of strengthening social support and teamwork cohesion within organizations to enhance employee performance.